The Role of School Committees and Community Supervision: School Performance in the Process of Improving the Quality of Education - Erwanto Guntoro; Siti Ruqoyyah; Albert Efendi Pohan; Sri Langgeng Ratna Sari (Academic Solution Publisher, 2025)
This study examines the influence of school committees and community supervision on school performance in the context of school supervision and improving the quality of education at SMPN 3 Numfor Barat. School committees play a vital role in the school management framework in various countries, responsible for offering support, overseeing activities, and promoting the interests of schools related to educational services for students. In contrast, community supervision requires the involvement of parents, residents, and other stakeholders in monitoring and assisting school performance. This study aims to investigate how partnerships between school committees and community supervision can affect the quality of education in schools. The application of a qualitative descriptive approach using interviews, observation, and documentation methods. Including a literature review, secondary data analysis, and field studies to assess how the role of school committees and community supervision affects the quality of education. The research findings indicate that the School Committee and community supervision at SMPN 3 Numfor Barat play a vital role through various initiatives that encourage active involvement of parents and the community. This can offer new perspectives for formulating more effective and responsive education policies that meet the requirements of schools and local communities. School committees also support central administration, provide resources, and improve teacher skills. It was determined that school committee involvement and community oversight had a significant impact on improving the quality of education, offering recommendations for strengthening the role of school committees and community oversight.